Comparisons and Refinements of Neonatal Oro-Tracheal Intubation Length Estimation Methods in Taiwanese Neonates - Peng, Chun-Chih; Chang, Hung-Yang; Tiong, Ngiik-Ping; Chang, Jui-Hsing; Hsu, Chyong-Hsin; Jim, Wai-Tim; Lin, Chia-Ying; Chen, Chia-Hui; Ko, Mary Hsin-Ju (Frontiers in Pediatrics, 2020)
Objective. This study aimed to evaluate the efficacy of Tochen’s formula (TF, body weight (kg) plus 6 cm), nasal septum to ear tragus length (NTL) + 1 cm, and Neonatal Resuscitation Program gestational age (NRP-GA) and body weight (NRP-BW)-based intubation table in estimating the oro-tracheal intubation length, and to improve the estimation efficacy using anthropometric measurements in Taiwanese neonates. Study design. This was a prospective observational study conducted at a neonatal intensive care unit in Taipei, Taiwan. One hundred intubated neonates were enrolled. The estimated intubation depth was defined as being mid-tracheal concordant if it placed the endotracheal tip between the upper border of the first and the lower border of the second thoracic vertebra. A linear regression model was used to analyze the relationships between mid-tracheal depth and body weight (BW), NTL and gestational age (GA), and to revise the NRP intubation tables using our results. Results. Overall, 56% of the neonates were born at a GA ≤ 28 weeks and 48% had a BW ≤ 1000 g. The overall mid-tracheal concordance rates for TF, NTL+1cm, NRP-GA, and NRP-BW estimations were 51.0%, 57.0%, 15.0%, and 14.0%, and in the infants with a BW ≤ 1000 g 56.3%, 56.3%, 8.3%, and 8.3% respectively. Our revisions of the NRP intubation tables based on the anthropometric measurements of our participants improved the efficacy of BW, GA, and NTL estimations to 63%, 44%, and 61%, respectively. Conclusion. TF and NTL+1cm were more reliable than NRP intubation tables in predicting the neonatal mid-tracheal length in neonates of all BW and GA. Considering morphological differences secondary to ethnicity, we recommend using these tailored recommendations during neonatal resuscitation in Asian neonates.